Zarys dziejów baliwatu brandenburskiego joannitów do końca XVI w. Wpływ reformacji na jego funkcjonowanie - Wasilkiewicz, Kamil (Studia Europaea Gnesnensia, 2018)
The article discusses selected fragments of history of the Bailiwick of Brandenburg, a jurisdiction of the Knights Hospitaller until the end of the 16th century, showing structural transformations it underwent over the centuries. Having outlined the social and political foundation of its functioning, the author presents the influence that the Reformation had on the bailiwick.